Respuesta de Bostryx conspersus y Succinea peruviana (Mollusca, Gastropoda) al evento "El Niño 1997-98" en las lomas de Lachay (Lima, Perú) - Ramírez, Rina (1999)
The analysis of the responses of two land snail species, Bostryx conspersus (Bulimulidae) and Succinea peruviana (Succineidae) from the Lomas of Lachay (Lima, Peru) to the changing environmental conditions before, during and alter "El Niño 1997-98" event is presented herein. Both species showed a remarkable response to the two picks of "El Niño 1997-98". During 1997, the start of the activity period of both species was delayed, while in the summer of 1998 neither B. conspersus nor S. peruviana had a periad of aestivation at all, on the contrary, the populations of both species had a demographic explosion. However, the intensity of the response of those species to "El Niño" was not the same. These changes in land snails population are positively related with other factor, the vegetable cover, changeable during "El Niño 1997-98".